COVID-19 and digital inequalities: Reciprocal impacts and mitigation strategies - Beaunoyer, Elisabeth; Dupéré, Sophie; Guitton, Matthieu J. (Computers in human behavior, 2020)
With more than three billion people in isolation, the status of digital spaces is switching from an amenity to a necessity, as they become not only the main way to access information and services, but also one of the only remaining vectors for economic, educational, and leisure activities as well as for social interactions to take place. However, not all are equals in terms of access to networks or connected devices, or when it comes to the skills required to navigate computerized spaces optimally. Digital inequalities were already existing, yet the COVID-19 crisis is exacerbating them dramatically. On the one hand, the crisis will worsen digital inequalities within the population. On the other hand, digital inequalities represent a major risk factor of vulnerability for exposure to the virus itself, and for the non-sanitary consequences of the crisis. Therefore, this paper aims at exploring the reciprocal impacts of the COVID-19 crisis and digital inequalities, and to propose operative solutions to help fight the nefarious consequences of the crisis. We first describe how digital inequalities are a determinant of health. We then investigate how COVID-19 can potentiate digital inequalities, and how digital inequalities potentiate vulnerability to COVID-19. Finally, in order to contribute to the mitigation of this crisis, we propose a set of multi-layered strategies focusing on actionability that can be implemented at multiple structural levels, ranging from governmental to corporate and community levels. •The COVID-19 pandemic is increasing digital inequalities.•Digital inequalities are increasing the vulnerability to the COVID-19 virus and to the consequences of the crisis.•The impact of digital inequalities on COVID-19 vulnerability should be central in the governmental responses.•Actionability-focused mitigation strategies targeting the individuals and the messages are proposed.